Pelatihan Petugas Taman dalam Pengelolaan Taman dalam Pengembangan Ruang Terbuka Hijau di Kota Depok - Ray March Syahadat; Priambudi Trie Putra; Daisy Radnawati; Siti Nurisjah; Fitria Nurhasanah (Institut Pertanian Bogor, 2019)
City park is one form of urban green open space. To maintain the city park in good condition, maintenance activities in the form of maintenance functions, shapes, and aesthetics are needed. In the park maintenance activities, park officers are needed as human resources who understand the maintenance activities. Depok Municipality in West Java Province is currently being intensively improving the quality of the park through park officer training activities. This public services activity consists of three stages i.e. field observations, training and tests to park officers, and evaluations to advise the stakesholders. The purpose of this article are to identify technical issues, to improve the practical knowledge of park officers, and to provide input to the management of parks in Depok Municipality. After the training, it was found that the park officers in Depok Municipality increased is their knowledge significantly. The absence of guidance on park management and unsustainable park design are technical problems faced by park officers. The Government of Depok Municipality needs to facilitate park officers with maintenance guidebooks, analyze labor needs, evaluate park quality, simplify garden design, make a list of existing trees and preserve the valuable old trees.